RISK FACTORS IN CHILDREN PRESENTING WITH DEVELOPMENTAL DELAY - Farid, Aisha; Maqbool, Shazia; Ullah, Ehsan; Ali, Anam; Farid, Zainab (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the risk factors in children presenting with developmental delay coming to the tertiary care hospital.Study Design: Case control study.Place and Duration of Study: The Children’s Hospital and Institute of Child Health, Lahore, from Nov 2018 to Jan 2019.Methodology: This was a case control study that included 280 children aged 6 months to 5 years. All children were assessed on ShaMaq Developmental Inventory in four equal groups of age ranges 6-10 months, 18-24 months, 3-3.5 years and 4-4.5 years. Demographic information was gathered through specially designed questionnaire that included risk factors such as gestational age, nutritional status of child, family income and others. Different risk factors were then compared between children with developmental delay and normal development.Results: Results found that there were more delays in male children (p